IPTEKS PENGENDALIAN INTERN DENGAN MENGGUNAKAN UNIT APU DAN PPT PADA PT. BANK SULUTGO - Mangangantung, Amanda N.; Ilat, Ventje (Universitas Sam Ratulangi, 2018)
The level of money laundering cases is increasingly high and the issue of terrorism is so high at this time. making companies engaged in financial services must be more careful so as not to become a means for criminals to carry out their actions. SulutGo Bank is a Bank whose share ownership is managed by the Regional Government of North Sulawesi Province. In accordance with OJK regulation No. 12 of 2017 which requires that the implementation of anti-money laundering and prevention of terrorism funding programs in the financial service provider sector, then Bank SulutGo establish the A and PPT Unit (Anti Money Laundering and Prevention of Terrorism Funding). With the establishment of the APU and PPT Unit, it is expected to be able to help the internal control system carried out by PT. SulutGo Bank. And it can also minimize the occurrence of crime of money laundering and funding of terrorist activities.Keywords :Â Internal Control, APU-PPT units